Phase II study of first-line bortezomib and cisplatin in malignant pleural mesothelioma and prospective validation of progression free survival rate as a primary end-point for mesothelioma clinical trials (European Organisation for Research and Treatment of Cancer 08052). - O'Brien, M; Gaafar, R; Popat, S; Grossi, F; Price, A; Talbot, D; Cufer, T; Ottensmeier, C; Danson, S; Pallis, A; Hasan, B; Van Meerbeeck, J; et al. (2013)
BACKGROUND: This was a prospective phase II study of cisplatin and bortezomib (CB) in the first line treatment of malignant pleural mesothelioma (MPM) with validation of progression free survival rate at 18 weeks (PFSR-18)(1) as primary end-point. METHODS: Chemotherapy-naïve patients with histologically proven MPM and performance status (PS) 0/1, were treated with cisplatin 75 mg/m(2) on day 1 and bortezomib 1.3mg/m(2) on days 1, 4, 8, 11 every 3 weeks. The primary end-point validation utilised the landmark method. RESULTS: Between 2007 and 2010 82 patients were entered. PFSR-18 was 53% (80% confidence intervals, CIs, 42-64%). The overall survival (OS) was 13.5 months (95% CI 10.5-15) with 56% (95% CI 44-66%) alive at 1 year. The median PFS was 5.1months (95% CI 3.3-6.5) and the response rate was 28.4% (95% CI 18.9-39.5%). The most frequent grade 3-4 toxicities were hyponatremia (46%), hypokalaemia (17%), fatigue (12.2%), thrombocytopenia (11%), neutropenia (9.7%) and neurotoxicity (motor, sensory, other: 1.2%, 8.5%, 2.4%). There were two toxic deaths (32 and 74days) due to acute pneumonitis and cardiac arrest. End-point validation showed that patients with no progression/progression at 18 weeks had median OS of 16.9/11.9 months, respectively. Hazard ratio was 0.46 (CI 0.32-0.67), logrank test and C-index were 0.007 and 0.60. CONCLUSION: The 50% PFSR-18 for CB was contained within the 80% CI for (42-64%). Therefore the null hypothesis could not be rejected. Accordingly this combination does not warrant further investigation. PFSR-18 was confirmed as a strong predictor of survival.